Perbandingan Kualitas Hidup berdasarkan Hasil Nilai SNOT-22 pada Penderita Rinosinusitis Kronik sebelum dan sesudah Terapi Irigasi Nasal dengan Larutan NaCl 0,9% - Zakiaturrahmi, Zakiaturrahmi; Syakirah, Raihan; TR, Teuku Husni (Fakultas Kedokteran Universitas Trisakti, 2025)
Background Chronic rhinosinusitis (CRS) is an inflammatory disease of the nasal mucosa and paranasal sinuses that lasts for 12 weeks or more. This disease often causes physical, emotional, and social disturbances in patients. CRS requires proactive treatment; therefore, nasal irrigation using 0.9% NaCl is considered a supportive therapy that can help manage CRS. This study aimed to evaluate changes in quality of life using the Sinonasal Outcome Test-22 (SNOT-22), a 22-question questionnaire, administered to CRS patients before and 10 days after nasal irrigation therapy with 0.9% NaCl solution. Methods This study was an observational analytic cross-sectional study involving 36 adult patients (18–60 years old) diagnosed with CRS at Zainoel Abidin Regional General Hospital, Banda Aceh. Data were obtained through the SNOT-22 questionnaire before and 10 days after nasal irrigation therapy. Results Statistical analysis showed a significant difference in SNOT-22 scores between before and 10 days after nasal irrigation therapy with 0.9% NaCl (p-value <0.05). This decrease in SNOT-22 scores reflects improvements in physical symptoms, such as nasal congestion and facial pain, as well as improvements in the patients' emotional and social well-being. Conclusions The average SNOT-22 scores of chronic rhinosinusitis patients before nasal irrigation therapy with 0.9% NaCl solution were high. This reflects the significant severity of chronic rhinosinusitis symptoms, both physical and psychosocial, before receiving the intervention.